Low energy collisions of spin-polarized metastable argon atoms with ground state argon atoms - Taillandier-Loize, T. (2019)
The collision between a spin-polarized metastable argon atom in Ar* (3p54s, 3P2, M = +2) state slightly decelerated by the Zeeman slower-laser technique and a co-propagating thermal ground state argon atom Ar (3p6, 1S0), both merged from the same supersonic beam, but coming through adjacent slots of a rotating disk, is investigated at the center of mass energies ranging from 1 to 10 meV. The duration of the laser pulse synchronised with the disk allows the tuning of the relative velocity and thus the collision energy. At these sub-thermal energies, the 'resonant metastability transfer' signal is too small to be evidenced. The explored energy range requires using indiscernibility amplitudes for identical isotopes to have a correct interpretation of the experimental results. Nevertheless, excitation transfers are expected to increase significantly at much lower energies as suggested by previous theoretical predictions of potentials 2g(3P2) and 2u(3P2). Limits at ultra-low collisional energies of the order of 1 mK (0.086 μeV) or less, where gigantic elastic cross sections are expected, will also be discussed. The experimental method is versatile and could be applied using different isotopes of Argon like 36Ar combined with 40Ar, as well as other rare gases among which Krypton should be of great interest thanks to the available numerous isotopes present in a natural gas mixture.